Faith, truth, and reason: the question of truth in “Caritas in Veritate” - Caviglia Marconi, Alessandro (2010)
This paper seeks to clarify the concept to Truth used in Caritas in veritate. This matter is approached considering that the theme of the truth has gained a special prominence, thus setting this as one of the biggest innovations of the encyclical letter of Pope Benedict XVI as opposed to the one of Pope Paul VI. Bearing in mind that the concept of Truth has a correlation with that of Reason, both concepts are analyzed in the paper under the light of other texts written by JosephRatzinger, and other opposing conceptions on Truth and Reason. Since these concepts find their  root in Greek philosophy, it is also necessary to address the problem of the Hellenization of the Christian message. Finally, some conclusions are drawn.